1983
DOI: 10.1177/004208598301800303
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Year-Round Schooling

Abstract: The benefits of year-round schooling are less than had been hoped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 1 publication
3
28
0
Order By: Relevance
“…In the face of overcrowding, there is a general consensus that multi-track year-round school calendars save in costs relative to traditional calendars, with estimates in the range of 5-15% (Daneshvary and Clauretie, 2001;CDE, 2007;Cooper et al, 2003;Merino, 1983). However, the question of the academic impact of multi-track year-round schools has not yet been thoroughly tackled by economists.…”
Section: Background and Calendar Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of overcrowding, there is a general consensus that multi-track year-round school calendars save in costs relative to traditional calendars, with estimates in the range of 5-15% (Daneshvary and Clauretie, 2001;CDE, 2007;Cooper et al, 2003;Merino, 1983). However, the question of the academic impact of multi-track year-round schools has not yet been thoroughly tackled by economists.…”
Section: Background and Calendar Discussionmentioning
confidence: 99%
“…With a large but inconclusive literature, many review papers attempt to synthesize what is known of the effects of year-round education on academic outcomes. Both Cooper et al (2003) and Merino (1983) discuss the inconclusiveness of the literature as arising from poor research methods. 6 Another synthesis of research conducted by the British Colombia Teachers Federation (Naylor, 1995) notes that many literature reviews are flawed in that they rely disproportionately on publications from organizations that passionately support year-round schools and tend to interpret results favorably.…”
Section: Background and Calendar Discussionmentioning
confidence: 99%
“…While past reviews of the research on year-round schooling are inconclusive (Merino 1983;Cooper et al 2003), recent work by Graves (2010Graves ( , 2011 indicates the year-round calendar may have detrimental effects on academic performance.…”
Section: Relevant Literature On School Schedule Changesmentioning
confidence: 99%
“…When exploring teacher attitudes in traditional and YRE workplaces, YRE teachers generally have a more positive outlook toward YRE than teachers on the traditional, agrarian school calendar (Costa, 1987;Elsberry, 1992;Fardig, 1992;Loyd, 1991;Merino, 1983;Nygaard, 1974;Pelavin, 1978;Prohm & Baenen, 1996). Shields & Oberg (2000) reported that after having some experience with a YRE calendar, 95% of the teachers preferred it to the traditional agrarian calendar.…”
Section: Intent To Turnover In the Educational Contextmentioning
confidence: 99%